Factors Related to the Occurrence of Osteochondral Lesions of the Talus by 3-dimensional Bone Morphology of the Ankle. Issue 3 (14th September 2018) - Teramoto, Atsushi; Shoji, Hiroaki; Kura, Hideji; Sakakibara, Yuzuru; Kamiya, Tomoaki; Watanabe, Kota; Yamashita, Toshihiko
Category: Ankle Introduction/Purpose: Repeated microtrauma is thought to play a major role in the occurrence of osteochondral lesions of the talus (OLTs), but much remains unknown. Two-dimensional assessments of the relationship between ankle bone morphology and OLTs are occasionally seen. The purpose of this study was to evaluate the bone morphology of the ankle in OLT 3-dimensionally using three-dimensional computed tomography (3DCT), and to investigate the factors related to the occurrence of OLTs. Methods: The subjects were 19 patients (19 ankles) who underwent surgery for medial OLTs (OLT group). They included 13 men and 6 women. A healthy group without ankle disease served as a control group with the same number of 19 ankles. Three-dimensional ankle joint models were made based on DICOM data obtained with CT images. In the 3D model, the medial malleolus articular surface and the tibial plafond surface, the medial surface of the trochlea of the talus, and the lateral surface of the trochlea of the talus were defined. The tibial axis-medial malleolus (TMM) angle, the medial malleolus surface area (MMA), the medial malleolus volume (MMV), and the anterior opening angle of the talus were measured 3-dimensionally and compared in the OLT and control groups. Results: The mean TMM angle was significantly larger in the OLT group (34.2 ± 4.4°) than in the control group (29.2 ± 4.8°; p = 0.002). The mean MMA was significantly smaller in the OLT group (219.8 ± 42.4 mm2) than in the control group (280.5 ± 38.2 mm2; p < 0.001). The mean MMV was significantly smaller in the OLT group (2119.9 ± 562.5 mm3) than in the control group (2646.4 ± 631.4 mm3; p = 0.01). The mean anterior opening angle of the talus was significantly larger in the OLT group (15.4 ± 3.9°) than in the control group (10.2 ± 3.6°; p < 0.001). Conclusion: It was shown with 3DCT measurements that, in medial OLT patients, the medial malleolus opens distally, the MMA and MMV are small, and the talus anterior opening angle was significantly larger than in controls. This study suggests the possibility that the 3D bone morphology of both the mortise and tenon of the ankle joint are closely related to the occurrence of OLTs.